2022
DOI: 10.1097/md.0000000000031363
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ginseng oral administration and ginseng injections on cancer-related fatigue: A meta-analysis

Abstract: Background: Up to 90% of patients who are under the active treatment suffer from cancer-related fatigue (CRF). CRF can persist about 10 years after diagnosis and/or treatment. Accumulating reports support that ginseng and ginseng injections are both potential drugs for the treatment of CRF but few studies put them together for analysis. Methods: Two reviewers independently extracted data in 3 databases (PubMed, Cochrane Library and China National Knowledge Infrastructure) from their inception to May 24, 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Similarly, this systematic review showed that these three TCM products might have a positive effect on CRF by improving some fatigue scale scores, cytokines level and blood tests compared with control group, and most patients showed no obvious adverse reaction after medication. Some findings also supported the antifatigue efficacy of these products in CRF patients [128,138]. According to the findings of this review, Kangai Injection, Buzhong Yiqi Decoction and Shenqi Fuzheng Injection are the TCM prescriptions worth considered for their role and potential benefits in treating CRF.…”
Section: Efficacy Of Tcm Products For Crfsupporting
confidence: 61%
“…Similarly, this systematic review showed that these three TCM products might have a positive effect on CRF by improving some fatigue scale scores, cytokines level and blood tests compared with control group, and most patients showed no obvious adverse reaction after medication. Some findings also supported the antifatigue efficacy of these products in CRF patients [128,138]. According to the findings of this review, Kangai Injection, Buzhong Yiqi Decoction and Shenqi Fuzheng Injection are the TCM prescriptions worth considered for their role and potential benefits in treating CRF.…”
Section: Efficacy Of Tcm Products For Crfsupporting
confidence: 61%